Analysis of the Electronic-Ionic polymer membrane. (2022) - Gagat, Nidhi; Umer Ansari, Mohd; Panwar, Varij
Abstract: Flexible materials are becoming increasingly important as wearable technology advances, and research shows. In this paper, we present and analyse the dielectric constant, conductivity, and dissipation factor of the membrane in the frequency band of 20 Hz to 10 MHz. The resultant membrane shows a decrease in the values of the dielectric constant as the frequency increases. The dielectric constant of the membrane was initially modest, but as the Carbon Nanofibers (CNF) was added to the membrane, the dielectric constant increased dramatically. The dielectric constant, AC conductivity, and dissipation factor were all determined using an impedance analyzer. We concluded in this study that by including CNF into the polymer matrix, we were able to achieve the greatest outcomes in terms of the dielectric, dissipation factor, and conductivity. The conductivity and dissipation factor are greatly affected by the carbon nanofibers (CNF) amount. The membrane can be used for flexible wearable devices, biomedical devices, in automotive industry and robotics.